DINAMIKA DAN STRATEGI KOLABORASI ETIS GURU DAN ORANG TUA DALAM MENGHADAPI TANTANGAN PENDIDIKAN ERA DIGITAL - Dini, Rikza; Setianing Sukma, Tri; Nuryanti, Setya; Khasanah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital age is revolutionizing education through technologies such as online platforms and AI, facilitating access to information but creating an imbalance in the roles of teachers and parents regarding ethical oversight, with risks of cyberbullying, age-inappropriate content, and negative impacts on students’ mental health and character particularly in Islamic education, which emphasizes noble moral values thereby necessitating collaboration between parents and teachers in education. This study aims to analyze the dynamics of ethical collaboration between teachers and parents and formulate comprehensive strategies to address the challenges of education in the digital age through a descriptive qualitative literature review approach using library research methods. The results indicate that ethical collaboration takes the form of real-time communication via WhatsApp and LMS, monitoring of online learning progress, and synergy in character development through shared regulations that prioritize digital literacy, data privacy, and cyberbullying prevention, accompanied by ethical principles such as polite virtual communication and respect for privacy. This approach addresses challenges related to differing expectations and ineffective communication through strategies involving agreed-upon rules and digital literacy training.